High molecular weight humic-like substances in carboneous aerosol of Ulaanbaatar city - Tserenpil, Shurkhuu; Fan, Xing Jung; Sapkota, Atindra; Chinzorig, Enkhmaa; Song, Jian Zhong; Liu, Cong Qiang (Mongolian Journal of Chemistry, 2018)
Total carbon content of the atmospheric suspended particulate matters consisted of as high as 89-93% organic carbon (OC) in Ulaanbaatar aerosol without showing seasonal variation. However, limited aerosol measurements have been conducted on these OC rich aerosols particularly for high molecular weight constituents. In order to address the gap above, abundance of high molecular weight humic-like substances (HULIS) in total suspended particulates (TSP) from Ulaanbaatar atmospheric aerosol were determined for the first time. HULIS molecular structure was characterised for different seasons using carbon content and UV absorbance measurements coupled with solid phase extraction methods. Although, HULIS contributions to water soluble organic fraction of the winter and summer aerosols were similar HULIS carbon concentration was higher in winter samples (9-37 mg·L-1) than in summer (2-6 mg·L-1). Consequently quantity of aromatic moieties and degree of aromaticity varied between seasons.